Unveiling a Malignant Oncocytic Adrenocortical Carcinoma: A clinico-radiological challenge resolved by immunohistology and a brief review of literature - Roy, Ashim; Kalita, Pranjal; Marbaniang, Evarisalin; Raphael, Vandana; Harris, Caleb; Kumar, Sumit; Lynser, Donboklang (Journal of Pathology of Nepal, 2025)
Oncocytic adrenocortical carcinoma (OACC) is a rare histopathological variant of adrenocortical carcinoma, a malignant tumor of adrenal cortical cells. The exact incidence of this unusual variant of ACC is unknown. It mainly occurs in the 5th decade of life with no gender predilection, without any established risk factor, and is characterised by the majority (>90%) of the tumor cells displaying oncocytic morphology. The patients mostly present with an abdominal mass with associated mass effects, or as an incidental finding detected during radiological evaluation for other reasons, and or occasionally with a functional status, usually hypercortisolism. It is an indolent variant with a lower stage, rare local invasion, delayed recurrence, and improved survivability, by virtue of which it differs from conventional adrenocortical carcinomas both clinically and prognostically. We present a case of non-functional left-sided oncocytic adrenocortical carcinoma in a 40-year-old female who was diagnosed radiologically as a high-grade malignancy, whereas histomorphology, along with immunohistochemistry, played a key role in diagnosis as OACC.